2021
DOI: 10.1002/eco.2274
|View full text |Cite
|
Sign up to set email alerts
|

Transverse distribution of cyanobacteria in a regulated urban river

Abstract: River eutrophication and CyanoHABs are severe problems that are often ignored because of high current speed and strong self‐purification. In this paper, Liangxi River, Taihu Basin, was selected as the research area. Combined with field investigation, a 2D water environment mathematical model was developed to simulate the chl‐a distribution in Liangxi River. An indicator (Transverse Distribution Center, TDC) and its normalized form (NTDC) to quantitatively represent material transverse distribution in rivers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous research on the effects of flow velocities on cyanobacterial growth had inconsistent results; the variations in experimental environments may be one of the reasons. Additionally, water flow alters the effect of light intensities on cyanobacteria by changing their distribution (Yan et al, 2021). This interaction between water flow and light intensity has not been thoroughly investigated in controlled laboratory settings, although some field studies have examined both water flow (or wind) and light intensities (Hamagami et al, 2019; Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the effects of flow velocities on cyanobacterial growth had inconsistent results; the variations in experimental environments may be one of the reasons. Additionally, water flow alters the effect of light intensities on cyanobacteria by changing their distribution (Yan et al, 2021). This interaction between water flow and light intensity has not been thoroughly investigated in controlled laboratory settings, although some field studies have examined both water flow (or wind) and light intensities (Hamagami et al, 2019; Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a range of critical flow velocities for cyanobacteria, varying from 0.06 to 0.3–0.5 m s −1 (Gao et al, 2007; Zhang et al, 2015). Cyanobacterial presence has been recorded under higher flow velocities, as evidenced in the Liangxi River of the Taihu Lake Basin, China (Yan et al, 2021), and the Yeongsan River, Korea (Kim et al, 2019), where outbreaks are more frequent during periods of high flow than in dry periods. The flow velocity in the Liangxi River can reach up to 17.72 cm s −1 (Wang et al, 2021), whereas in the Yeongsan River, a maximum of 49.80 cm s −1 near the Chucksan weir has been recorded (Sin & Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%